A new Oliveriana (Orchidaceae: Oncidiinae) from Ecuador - Dalström, Stig (Lankesteriana: International Journal on Orchidology, 2016)
A new species of Oliveriana is described and illustrated. It is compared with and distinguished from all other listed members of the genus by a unique combination of distinct features, such as the extremely elongate and narrow leaves, and a flower with a fleshy triangular lip. It is speculated here that this new species may be self-pollinating due to the high success of seed pod production, which is unusual among genera in Oncidiinae.